Evaluation the discomfort level for students Polytechnic Kuching Sarawak sitting on chairs - Ali, M.; Karuppiah, K; Salit, M.S.; Ahmed, A.S. (Malaysian Public Health Physicians Association, 2016)
This study was conducted to evaluate the discomfort level of students from the Polytechnic Kuching Sarawak while they were sitting on chairs. Polytechnic Kuching students (n=500) completed a set of questionnaires utilizing a survey form which showed the body chart discomfort using Borg's CR-10 Scale. The students was asked to identify body areas experiencing discomfort and to rate this discomfort using score rating groups (0 to 5) where score 0-1.99 = No discomfort (1), score 2.00-3.99 = Discomfort (2) and score 4.00-5.00 = Very uncomfortable (3). The evaluation of seating discomfort levels showed acceptable levels for the students and possible outstanding problems. Students were asked to rank over an order 10 statements about comfort and choose three responses which gave the most consistent equal interval scale. The results showed that the main response of discomfort indicated the students felt cramped, stiff, numb, sore and tender muscle, unbearable pain, barely comfortable and uncomfortable. This project was identified to evaluate the comfort level for classrooms chairs of polytechnic students. Overall, there was a significant discomfort level for the students whilst sitting on chairs and a possible solution put forward is to design a new type of classroom chair made of natural fibre reinforced composite.